2-D image reconstruction of photoacoustic endoscopic imaging based on time-reversal. (1st September 2016) - Zheng, Sun; Duoduo, Han; Yuan, Yuan
Abstract: Backgrounds: Photoacoustic endoscopic (PAE) imaging is a rapidly emerging interventional imaging modality for identification and characterization of intraluminal pathological tissues. Since the scanning aperture of PAE is enclosed in the lumen, image reconstruction techniques used in photoacoustic tomography (PAT) can not be directly applied. Objective: The purpose of this work is to design an image reconstruction method based on time-reversal (TR) for a PAE imaging catheter equipped with a single-element NFU transducer with circular scanning. Methods: Firstly, the back-propagation of photoacoustic waves emitted from the tissue absorbers was modeled and simulated. Then, two-dimensional (2-D) grayscale images of the acoustic pressure distribution were obtained displaying the morphological structure of luminal cross-sections. A computer-simulated vessel phantom embedded with atherosclerotic plaques was used to validate and quantitatively evaluate the method. Result: The structural similarity (SSIM) of the images reconstructed with TR is comparable to algebraic reconstruction technique (ART), which is at least 65% higher than filtered back-projection (FBP). The time cost of TR is about 16 times that of FBP and 1/4 of ART under the same test condition. Conclusion: The reconstructed image quality may degrade when the photoacoustic data are incomplete due to sparse measuring locations and limited-view scanning. The spline interpolation can be used to improve the image quality and eliminate artifacts. Highlights: We propose an image reconstruction method based on TR. It is for a PAE catheter with a single-element NFU transducer with circular scanning. The back-propagation of PA waves emitted from the tissues was modeled and simulated. The collected PA pressure data was interpolated to improve the image quality. The SSIM is at least 65% higher than FBP, while the time cost is 16 times of FBP.